A NUMRICAL SOLUTION FOR MAGNETOHYDRODYNAMIC STAGNATION-POINT FLOW TOWARDS A STRETCHING SHEET - et. al., Lalitkumar Shantilal Narsingani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Steady two-dimensional stagnation-point flow of an incompressible viscous electrically con- ducting fluid over a flat deformable sheet is investigated when the sheet is stretched in its own plane with a velocity proportional to the distance from the stagnation-point. Using similarity variables, the governing partial differential equations are transformed into a set of non-dimensional ordinary differential equations. These equations are then solved numerically using Spline collocation method. In the present reported work the effect of magnetic field parameter on flow have been discussed.